Molecular phylogeny of the neritidae (gastropoda: neritimorpha) based on the mitochondrial genes cytochrome oxidase i (coi) and 16s rrna (2013)
The family Neritidae has representatives in tropical and subtropical regions that occur in a variety of environments, and its known fossil record dates back to the late Cretaceous. However there have been few studies of molecular phylogeny in this family. We performed a phylogenetic reconstruction of the family Neritidae using the COI (722 bp) and the 16S rRNA (559 bp) regions of the mitochondrial genome. Neighbor-joining, maximum parsimony and Bayesian inference were performed.The best phylogenetic reconstruction was obtained using the COI region, and we consider it an appropriate marker for phylogenetic studies within the group. Consensus analysis (COI +16S rRNA) generally obtained the same tree topologies and confirmed that the genus Nerita is monophyletic. The consensus analysis using parsimony recovered a monophyletic group consisting of the genera Neritina, Septaria, Theodoxus, Puperita, and Clithon, while in the Bayesian analyses Theodoxus is separated from the other genera. The phylogenetic status of the species from the genus Nerita from the Colombian Caribbean generated in this study was consistent with that reported for the genus in previous studies. In the resulting consensus tree obtained using maximum parsimony, we included information on habitat type for each species, to map the evolution by habitat. Species of the family Neritidae possibly have their origin in marine environments, which is consistent with conclusions from previous reports based on anatomical studies.Filogenia molecular de la familia Neritidae (Gastropoda: Neritimorpha) con base en los genes mitocondriales citocromo oxidasa I (COI) y 16S rRNALa familia Neritidae cuenta con representantes en regiones tropicales y subtropicales adaptadas a diferentes ambientes, con un registro fósil que data para finales del Cretáceo. Sin embargo no se han realizado estudios de filogenia molecular en la familia. En este estudio se realizó una reconstrucción filogenética de la familia Neritidae utilizando las regiones COI (722 pb) y 16S rRNA (559 pb) del genoma mitocondrial. Se realizaron análisis de distancias de Neighbor-Joining, Máxima Parsimonia e Inferencia Bayesiana. La mejor reconstrucción filogenética fue mediante la región COI, considerándola un marcador apropiado para realizar estudios filogenéticos dentro del grupo. El consenso de las relaciones filogenéticas (COI+16S rRNA) permitió confirmar que el género Nerita es monofilético. El consenso del análisis de parsimonia reveló un grupo monofilético formado por los géneros Neritina, Septaria, Theodoxus, Puperita y Clithon, mientras que en el análisis bayesiano Theodoxus se encuentra separado de los otros géneros. El resultado en las especies del género Nerita del Caribe colombiano fue consistente con lo reportado para el género en estudios previos. En el árbol resultante del análisis de parsimonia se sobrepuso la